Prismatic Silver Nanoparticles Decorated on Graphene Oxide Sheets for Superior Antibacterial Activity - Thi Tuong Vi Truong; Chien-Chang Chen; Selvaraj Rajesh Kumar; Chih-Chien Hu; Dave W. Chen; Yu-Kuo Liu; Shingjiang Jessie Lue (MDPI AG, 2022)
Spherical silver nanoparticles (Ag NPs) and silver nanoprisms (Ag NPrsms) were synthesized and decorated on graphene oxide (GO) nanosheets. The Ag contents were 29% and 23% in the GO-Ag NPs and GO-Ag NPrsms, respectively. The Ag NPrsms exhibited stronger (111) crystal signal than Ag NPs. The GO-Ag NPrsms exhibited higher Ag (I) content (75.6%) than GO-Ag NPs (69.9%). Increasing the nanomaterial concentration from 25 to 100 µg mL−1 improved the bactericidal efficiency, and the antibacterial potency was in the order: GO-Ag NPrsms > GO-Ag NPs > Ag NPrsms > Ag NPs > GO. Gram-positive Staphylococcus aureus (S. aureus) was more vulnerable than Gram-negative Escherichia coli (E. coli) upon exposure to these nanomaterials. The GO-Ag NPrsms demonstrated a complete (100%) bactericidal effect against S. aureus at a concentration of 100 µg mL−1. The GO-Ag composites outperformed those of Ag or GO due to the synergistic effect of bacteriostatic Ag particles and GO affinity toward bacteria. The levels of reactive oxygen species produced in the bacteria-nanomaterial mixtures were highly correlated to the antibacterial efficacy values. The GO-Ag NPrsms are promising as bactericidal agents to suppress biofilm formation and inhibit bacterial infection.